MSCs Contribute to the Conversion of Ly6Chigh Monocytes into Ly6Clow Subsets under AMI - Wenbin Lu; Genshan Ma; Zulong Sheng; Qingjie Wang; Lijuan Chen; Junhua Qi; Ronghui Shi; Jingjing Ji; Zhenjun Ji; Qiming Dai (Stem Cells International)
Background. Ly6Chigh monocytes are inflammatory cells that accumulate in an infarcted myocardium, and Ly6Clow monocytes are believed to be reparative and curb myocardial remodeling. NR4A1 is a novel target for modulating the inflammatory phenotype of monocytes during atherogenesis. Objectives. We aimed to investigate whether MSCs can contribute to the heterogeneity of Ly6Chigh monocytes differentiated into Ly6Clow monocytes and whether this regulation is related to nuclear receptor NR4A1. Methods. Ly6Chigh/low monocytes were first cocultured with MSCs. C57BL/6CX3CR1-/- mice and C57BL/6 wild-type mice were then used to construct AMI models, and survival functions in the two groups were further compared. Ly6Chigh/low monocytes in circulation and in MI tissue of C57BL/6CX3CR1-/- AMI mice with or without MSC transplantation were determined by flow cytometry at day 1 and day 3. NR4A1 expression was further determined by Western blot. Apoptosis of cardiac myocytes in the infarct border zone at day 3 and day 7 was identified by TUNEL kits. Angiogenesis in the AMI heart at day 7 and day 21 was determined through immunohistochemistry by CD31. Results. We first demonstrated that the percentage of Ly6Clow monocytes increased greatly after 3 days of coculture with MSCs (12.8%±3.77% vs. 3.69%±0.74%, p<0.001). The expression of NR4A1 in Ly6Chigh/low monocytes was also significantly elevated at that time (1.81±0.46 vs. 0.43±0.09, p<0.001). Following AMI, the percentage of circulating Ly6Clow monocytes in C57BL/6CX3CR1-/- mice was significantly lower than that in C57BL/6 wild-type mice (4.36%±1.27% vs. 12.17%±3.81%, p<0.001). The survival rate of C57BL/6CX3CR1-/- mice (25%) was significantly lower than that of C57BL/6 wild-type mice (56.3%) after AMI (χ2=4.343, p=0.037). After MSCs were transplanted, we observed a significant increase in Ly6Clow monocytes both in circulation (16.7%±3.67% vs. 3.22%±0.44%, p<0.001) and in the MI heart (3.31%±0.69% vs. 0.42%±0.21%, p<0.001) of C57BL/6CX3CR1-/- mice. Western blot analysis further showed that the expression level of NR4A1 in the MI hearts of C57BL/6CX3CR1-/- mice increased significantly under MSC transplantation (0.39±0.10 vs. 0.11±0.04, p<0.001). We also found significantly decreased TUNEL+ cardiac myocytes (15.45%±4.42% vs. 22.78%±6.40%, p<0.001) in mice with high expression levels of NR4A1 compared to mice with low expression levels. Meanwhile, we further identified increased capillary density in the infarct zones of mice with high expression levels of NR4A1 (0.193±0.036 vs. 0.075±0.019, p<0.001) compared to mice with low expression levels 21 days after AMI. Conclusions. MSCs can control the heterogeneity of Ly6Chigh monocyte differentiation into Ly6Clow monocytes and further reduce inflammation after AMI. The underlying mechanism might be that MSCs contribute to the increased expression of NR4A1 in Ly6Chigh/low monocytes.